Lone women : a novel - LaValle, Victor, 1972- (New York : One World, 2023)
"Adelaide Henry carries an enormous steamer trunk with her wherever she goes. It's locked at all times. Because when the trunk is opened, people around her start to disappear... The year is 1914, and Adelaide is in trouble. Her secret sin killed her parents, and forced her to flee her hometown of Redondo, California, in a hellfire rush, ready to make her way to Montana as a homesteader. Dragging the trunk with her at every stop, she will be one of the "lone women" taking advantage of the government's offer of free land for those who can cultivate it, except that Adelaide isn't alone. And the secret she's tried so desperately to lock away might be the only thing keeping her alive."--
Keywords: Family secrets -- Fiction; Murder -- Fiction; African Americans -- Fiction; Frontier and pioneer life -- Fiction; West (U.S.) -- Fiction; Historical fiction; Western fiction; Fantasy fiction; Horror fiction